Glycogen supports glycolytic plasticity in neurons - Milind Singh; Aaron D. Wolfe; Anjali A. Vishwanath; Anastasia Tsives; Ian J. Gonzalez; Sarah E. Emerson; Richard Goodman; Daniel Colón-Ramos (Proceedings of the National Academy of Sciences, 2025)
Glycogen is the largest energy reserve in the brain, but the specific role of glycogen in supporting neuronal energy metabolism in vivo is not well understood. We established a system in Caenorhabditis elegans to dynamically probe glycolytic states in single cells of living animals via the use of the glycolytic sensor HYlight and determined that neurons can dynamically regulate glycolysis in response to activity or transient hypoxia. We performed an RNAi screen and identified that PYGL-1, an ortholog of the human glycogen phosphorylase, is required in neurons for glycolytic plasticity. We determined that neurons employ at least two mechanisms of glycolytic plasticity: glycogen-dependent glycolytic plasticity (GDGP) and glycogen-independent glycolytic plasticity. We uncover that GDGP is employed under conditions of mitochondrial dysfunction, such as transient hypoxia or in mutants for mitochondrial function. We find that the loss of GDGP impairs glycolytic plasticity and is associated with defects in synaptic vesicle recycling during hypoxia. Together, our study reveals that, in vivo, neurons can directly use glycogen as a fuel source to sustain glycolytic plasticity and synaptic function.